Is there a role for proton pump inhibitor prophylaxis in haematology patients?. Issue 6 (11th June 2019) - Leitinger, Emma; Hui, Lisa; Grigg, Andrew
Abstract: While proton pump inhibitors (PPI) are widely prescribed as prophylaxis in selected haematology inpatient and outpatients, an informal survey of haematology units around Australia found wide variations in the specific indications for their use. This is consistent with a literature review which showed a paucity of robust evidence to support their use, specifically in chemotherapy‐induced mucositis, thrombocytopenia or administration of high dose glucocorticosteroids in the absence of additional risk factors. Rationalising PPI prescribing is clinically important from both a cost and safety perspective, given the emerging evidence of adverse events associated with prolonged PPI administration. A review of prescribing practices at our institution over a 14‐month period found that approximately 60% of myeloma, lymphoma and autograft patients received PPI prophylaxis during and beyond chemotherapy without an accepted indication. We encourage institutions to review their PPI prescribing practices with the intent of rationalising their use, and to conduct studies aiming to fill the substantial gaps in our knowledge.